Penguatan Pentingnya Pendidikan Dalam Memutus Mata Rantai Kemiskinan - Putri, Mutiara; Suwarni, Suwarni; Soleh, Ahmad; Susena, Karona Cahya; Gayatri, Ida Ayu Made Er Meytha (Jurnal Dehasen Untuk Negeri, 2025)
Education plays an important role in shaping the character and future of children. Poverty is a phenomenon that has become a major problem for many countries; both developed and developing countries. Poverty has always been a part of the social dynamics of society which is sunnatullah as well as a “disease” that must be cured through various approaches and development policies. This activity aims to provide motivation and understanding of the importance of education. By using descriptive qualitative methods / data collection by means of interviews, documentation and direct observation. The results of this community service are an increase in motivation in the children of Bina Remaja Harapan Bengkulu Orphanage.